1999
DOI: 10.1136/bjsm.33.3.178
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the aerobic-anaerobic transition in elite cyclists during incremental exercise with the use of electromyography.

Abstract: Objectives-To investigate the validity and reliability of surface electromyography (EMG) as a new non-invasive determinant of the metabolic response to incremental exercise in elite cyclists. The relation between EMG activity and other more conventional methods for analysing the aerobic-anaerobic transition such as blood lactate measurements (lactate threshold (LT) and onset of blood lactate accumulation (OBLA)) and ventilatory parameters (ventilatory thresholds 1 and 2 (VT 1 and VT 2 )) was studied. Methods-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
144
4
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(174 citation statements)
references
References 30 publications
20
144
4
6
Order By: Relevance
“…The stages where there was identification of EMGTh corroborate the bibliographic findings which was found around 30 and 40% of 1RM [13,15], this values were also found in this study, however, Lucia et al [16] had shown on a progressive test of a cyclic modality the anaerobic threshold at intensities close to 60 to 70% of VO 2max , suggesting that the EMGTh is related to the activity type and protocol, yet having a highly reproducible and significant ICC according to Lucia et al [17], the EMGTh shows no significant difference, and shows significant correlation to the lactate and ventilatory thresholds expressed in % VO 2max for heart transplanted.…”
Section: Discussionsupporting
confidence: 92%
“…The stages where there was identification of EMGTh corroborate the bibliographic findings which was found around 30 and 40% of 1RM [13,15], this values were also found in this study, however, Lucia et al [16] had shown on a progressive test of a cyclic modality the anaerobic threshold at intensities close to 60 to 70% of VO 2max , suggesting that the EMGTh is related to the activity type and protocol, yet having a highly reproducible and significant ICC according to Lucia et al [17], the EMGTh shows no significant difference, and shows significant correlation to the lactate and ventilatory thresholds expressed in % VO 2max for heart transplanted.…”
Section: Discussionsupporting
confidence: 92%
“…Results of our research and the researches of A. Lucia [14], F. Hug [13] showed the presence of two electromyography thresholds (EMGT1 and EMGT2). The authors explain the presence of two thresholds in elite sportsmen by their ability to switch in work different types of muscle fibers (transitive and glycolitic) in response to increase of load's intensity up to definite level.…”
Section: Discussionsupporting
confidence: 59%
“…Analysis of recent data [13,14,16] and our own researches [8,9] permitted to determine purposefulness of SEMG application for assessment of NMS functional potentials in cyclic kinds of sports sportsmen.…”
mentioning
confidence: 99%
“…This effect has been subject to extensive research [5,7]; however, the underlying mechanisms remain unclear. [10][11][12]. The integrated electromyographic anaerobic threshold is regarded as the inflection point at which an abrupt non-linear increase in the integrated electromyogram occurs, representing the changes in the motor unit (MU) recruitment and/or MU firing frequency during incremental exercise [13].…”
Section: Study Protocol and Designmentioning
confidence: 99%